Quality of Life after Free Fibula Flap Reconstruction of Segmental Mandibular Defects - Löfstrand, Jonas; Nyberg, Marcus; Karlsson, Therese; Thórarinsson, Andri; Kjeller, Göran; Lidén, Mattias; Fröjd, Victoria (Journal of Reconstructive Microsurgery, 2018)
Background Free fibula flap (FFF) is considered gold standard in the reconstruction of mandibular defects. Despite the frequent use, patients' quality of life (QoL) after reconstruction has been sparsely investigated. This study aims to evaluate QoL and outcomes in patients who have undergone FFF reconstruction of segmental mandibular defects.Methods A retrospective cohort study of consecutive patients (n = 73) operated at a single center during the years 2000 to 2014 was performed. Charts were reviewed and all living patients (n = 41) were invited to fill out three quality of life questionnaires (QLQ): SF-36, EORTC QLQ-C30, and QLQ-H&N35. Factors associated with poor outcome were derived from regression models and the results of the QLQs were compared with Swedish reference populations. Subgroup analysis was performed for two groups depending on reconstructive indication: cancer and osteoradionecrosis (ORN).Results The response rate of the QLQs was 93%. General QoL did not differ from reference populations, but the study group had significantly larger proportions of poor functioning patients in three domains in EORTC QLQ-C30: global health status, role functioning, and social functioning. Patients also reported a high incidence of poor functioning/high symptom burden in EORTC QLQ-H&N35, with a significantly higher frequency in the ORN group compared with the cancer group for the domains “swallowing” and “social eating.” The overall flap success rate was 92% and complication rate was 48%. Previous surgery had a significant association with reoperation due to bleeding, and longer duration of surgery was significantly associated with local infection.Conclusion When evaluated with validated QLQs, most patients experienced persistent functional loss in one or several domains, but still perceived a general QoL that is close to that of reference populations. Patients having ORN as the indication for surgery, as compared with cancer, reported a higher frequency of poor functioning patients in disease-specific QoL domains.
Keywords: head and neck cancer; osteoradionecrosis; fibula flap; microsurgery; quality of life; mandibular reconstruction